Development of optically sensitive liver cells. (June 2018) - Vajanthri, Kiran Yellappa; Yadav, Parul; Poddar, Suruchi; Mahto, Sanjeev Kumar
Highlights: Generation of optically governed HepG2 cells through the integration of a membrane-bound ChR2 protein by transfection. Cationic liposome-mediated delivery yields transfection efficiency of 41.26% and 46.04% in HepG2 and NIH 3T3 cells, respectively. Co-culture of generated HepG2 and NIH-3T3 cells may serve as prospective models for toxicological and pharmacological studies. Abstract: Optogenetics is a new and emerging field that involves techniques of optics and genetic engineering to influence cellular functionality. In this work, we have successfully incorporated a non-selective cationic channel channelrhodopsin-2 (ChR2) into human hepatocellular carcinoma (HepG2) cells. A plasmid construct AAV-CAG-ChR2-GFP was used for liposomal transfection into the cells. ChR2 is a light sensitive membrane channel that opens upon illumination with blue light. Plasmid DNA isolation from E. coli XL 10 gold bacteria by alkaline lysis method resulted in a DNA concentration of 1150 μg/mL. A significant difference (p < 0.05) was observed between the fluorescent intensities of transfected cells and the control. The percentage of transfected cells was estimated to be 41.26%. Overall, the study delivers an optimized methodology to produce the transfected HepG2 cells that can be controlled with the light stimulation. Although ChR2 has mostly been associated with excitable cells, we anticipate that its presence into HepG2 cells may also result changes in biological functionalities by modulating the concentration of cations inside the cell. Furthermore, the transfected HepG2 cells can be co-cultured with fibroblasts such as NIH 3T3 to form liver spheroids that can serve as models for toxicological and pharmacological studies.